2016
DOI: 10.1097/mca.0000000000000419
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of nonculprit coronary atherosclerotic plaques assessed by serial virtual histology intravascular ultrasound in patients with ST-segment elevation myocardial infarction and chronic total occlusion

Abstract: ObjectiveThe pathophysiology and natural course of coronary nonculprit plaques remain unclear. We investigated whether the short-term natural course of nonculprit plaques differs between ST-segment elevation myocardial infarction (STEMI) and chronic total occlusion (CTO) patients.MethodsWe performed serial virtual histology intravascular ultrasound on nonculprit plaques in 26 STEMI and 11 CTO lesions at baseline and the 6-month follow-up.ResultsAt baseline, more lesions in the STEMI group were virtual histolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Also, evaluating the entire coronary vasculature with these tools is a significant clinical burden to both the clinician and patient. [ 18 ] Therefore, we still need more feasible angiographic standards for lesion evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Also, evaluating the entire coronary vasculature with these tools is a significant clinical burden to both the clinician and patient. [ 18 ] Therefore, we still need more feasible angiographic standards for lesion evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…[51] Kang et al [52] found that an elevated plaque structural stress (PSS) was more likely associated with and the presence of VH-TCFA at 12-month follow-up and the VH-derived PSS was increased in plaques responsible for MACE. Kang et al [53] showed that nonculprit lesions in ST-segment elevation myocardial infarction (STEMI) patients were more unstable at the baseline compared with those in chronic total occlusion (CTO) patients, the diagnosis of STEMI and a large NC volume were predictors of evolution to a TCFA. Several studies had investigated the impact of plaque components on no-reflow after PCI in patients with ACS.…”
Section: Application Of Vh-ivus In the Interventional Therapy Of Svgdmentioning
confidence: 99%
“…CTO in acute myocardial infarction (AMI) has poor outcomes despite successful primary percutaneous coronary intervention (PCI) [2,3]. Although the pathophysiology of AMI and of CTO is different, it may be challenging to identify the culprit lesion in patients with multivessel diseases, particularly in an emergency situation [4]. We describe two cases of emergency PCI using different approaches that resulted in complications in patients with AMI and concurrent CTO.…”
Section: Introductionmentioning
confidence: 99%